A speckle method of gray level pseudocoloring - Rabal, Héctor J. (1981)
A simple method of pseudocoloring gray level images is proposed. It is based on Young’s fringes modulated speckle encoding of images. Reconstruction from a photographic register is obtained using two light beams with different wavelengths at the same time. Pseudocoloring is produced by the superposition of a (diffracted) direct image in one color and a (directly transmitted) contrast reversed image in another color.